Warmth and Familiarity of Transportation Demand Omotenashi in the Jam Gadang Area of Bukittinggi - Agustin, Imma Widyawati; Safitri, Fanny; Hariyani, Septiana; Waloejo, Budi Sugiarto (Fakultas Teknik Universitas Brawijaya, 2025)
One of the busiest locations of Bukittinggi is the Jam Gadang region, which is distinguished by land use areas that are mostly used for trade, services, and tourism. This area's level of appeal is not directly correlated with the amount of urban infrastructure, such as pedestrian walkways, which are abused by shopkeepers or street vendors who set up shop along them and by motorized vehicle users who park illegally on them, endangering the safety of both pedestrians and vehicle users. This study aims to examine the factors of familiarity and warmth in the Jam Gadang area. The warmth component is analyzed by determining the distinctiveness of the Jam Gadang area through its physical, social, and historical appeal. The familiarity component is examined by considering the features and effectiveness of on-street parking in the Jam Gadang area, as well as the number of public transportation options available. While the familiarity aspect of on-street parking will be studied using Important Performance Analysis (IPA) to assess service performance, and then followed by Quality Function Deployment (QFD) analysis to determine the priority of enhancing on-street parking performance, the warmth aspect will be analyzed using descriptive analysis. Frequency distribution analysis will be used to examine the familiarity factor of interacting public transportation users. The findings demonstrate the importance of managing the pedestrian path in the Jam Gadang area by incorporating the Omotenashi concept, which emphasizes familiarity and warmth. Physical attractiveness is highest on Ahmad Yani street, which has a total attractiveness value of 93, is characterized by the variety of building functions on this road.